Childhood pyoderma gangrenosum: diagnosis often missed - Magar, Suvarna; Siddiquie, Saeed; Kale, Anjali; Valecha, Aashna (International Journal of Contemporary Pediatrics, 2018)
We present a 10-year-old male child who presented with 2 months history of fever and extensive ulceration over both lower limbs and buttocks. The new lesions were bullous and pustular, so working diagnosis of bullous impetigo was considered. WBC count showed mild anemia and neutrophilic leucocytosis. Peripheral smear showed neutrophilia, adequate platelets and normal lymphocytes. Blood culture and pus culture were sterile. Stool for occult blood was negative, liver function tests were normal. Mantoux test was negative. Serum immunoglobulins were normal and HIV, HBsAg tested negative. Skin biopsy showed foci of granulomatous inflammation with neutrophilic infiltration. With persistent neutrophilia and neutrophilic infiltration of ulcers, pyoderma gangrenosum was kept as diagnosis. The child was started on local steroid application and oral prednisolone 1 mg/kg/day. Wthin 2 days of oral steroids child became afebrile. Ulcers started healing and neutrophila also normalized. In view of reappearance of fever, immunosuppressive, closporin was started, after which child responded well and ulcers healed completely. So, in conclusion, we report a paediatric case of pyoderma gangrenosum which poses diagnostic difficulty, particularly to non-dermatologists. The dramatic response to steroid and cyclosporine helped cure the ulcers and remit the disease and sufferings.